A new species, Dichomeris stellata sp. nov. (Lepidoptera: Gelechiidae), with a checklist of the genus from Korea - Park, Jinsung; Cho, Ha-Young; Kim, Sora (Zootaxa, 2025)
This study reports the discovery of a new species, Dichomeris stellata sp. nov., and provides a checklist of Dichomeris species from Korea. The description and diagnostic morphological characteristics of the new species are provided, along with detailed illustrations of the adults and genitalia. In addition, the NJ tree based on COI sequences of the new species and congeners also supports the novelty of the taxon presented here as D. stellata sp. nov.